Assessment Of The Implementation Of Contents For Secondary School Biology Curriculum In Three States In Southwest, Nigeria - Akinnodi, Oladamola Dickson (Advances in Social Sciences Research Journal, 2020)
The study assessed the implementation of contents for secondary school biology curriculum in three states in Southwest, Nigeria. The descriptive research design of the survey type was used in this study. The population of the study comprised all Biology teachers in all the public secondary schools in Ondo, Osun and Oyo States. The samples for the study consisted of 180 biology teachers drawn from 180 public secondary schools in the three states. The sample was selected using multistage sampling procedure. An instrument tagged Inventory on Implementation of Biology Curriculum (IIBC) was used for collecting the data for the study. The validation process was exempted since an inventory was used. The responses obtained were collated and analysed using descriptive and inferential statistics. The findings of the study revealed that Biology curriculum contents were not fully covered. It was also revealed that most of the schools do not meet the recommended standard of at least 2 periods per week for practical work in Biology. It was further revealed that the implementation of the contents of Biology curriculum in secondary schools do not differ among the three states considered in this study. It was recommended among others that Biology teacher should intensify efforts to see that the biology curriculum contents are covered and implemented.